Agricultural Growth Diagnostics: Identifying the Binding Constraints and Policy Remedies for Bihar, India. Issue 2 (December 2021) - Kannan, Elumalai; Pohit, Sanjib
Agriculture plays a significant role in economic development of underdeveloped regions. Multiple factors influence the performance of agricultural sector but a few of these have a strong bearing on its growth. This study develops a growth diagnostics framework for agricultural sector in Bihar, located in eastern India, to identify the most binding constraints. The study results show that poor functioning of agricultural markets and low-level of crop diversification are the important reasons for low agricultural growth in Bihar. Rise in price instability of agricultural produces indicates a weak price transmission across the markets even after repealing the Agricultural Produce Market Committee Act. Poor market linkages and non-functioning producer collectives at village-level affect the farmers' motivation for undertaking crop diversification. Hence, policy suggestions to overcome these binding constraints include the state provisioning of basic market infrastructure to attract private investment in agricultural marketing, strengthening the Farmer Producer Organisations, and framing a comprehensive policy on crop diversification.